Optimal Control of Reservoir Operation Policy under Different Inflow Probabilities: A Case Study of Mohamed V Dam, Morocco - Harraki, Wafae El; Ouazar, Driss; Harraki, Imad El; Bouziane, Ahmed (Journal of Environmental Accounting and Management, 2026)
This paper examines reservoir operation optimization considering probabilistic inflows. Optimal control of this model is obtained using Pontryagin’s Minimum Principle. The formulated problem includes non-linear equations on the state variables related to evaporation, stochastic inflows derived from historical time series and target ending storage constraint. Mohamed V dam is used as a case study to derive optimal operating rules through numerical simulation. The effect of inflows variability is demonstrated and a risk assessment of initial storage’s variation is discussed. A benchmark based on Genetic Algorithms showed the developed model’s performance. 9% of improvement for the low inflows scenario, are achieved.